(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2013)
The purpose of this research study was to develop 5-fluorouracil compression coated tablets by using biodegradable polysaccharide polymer locust bean gum (LBG) and hydroxyl propyl methyl cellulose (HPMC) as coating materials. The fast disintegrating core tablets containing 50 mg of 5-fluorouracil were compression coated with LBG and HPMC in different ratios (8:1, 7:2 and 6:3) with a coat weight of 300, 400 and 500 mg. In vitro dissolution data indicated that the formulation (CLH63) with a coat weight of 500 mg containing LBG and HPMC in the ratio 6:3 gave the best release profile (0% in first 5 hour and 96.18% in 24 hours). DSC and FTIR results indicated no possibility of interaction between drug and polymers or other excipients. In vivo human X-ray studies revealed that formulation CLH63 was able to resist breakdown in the stomach and small intestine. The disintegration of the tablet occurred in the colon between 8 to 16 hours of post dose. By the present study, it can be concluded that the LBG and HPMC based compression coated tablets of 5-fluorouracil will be useful strategy for colonic delivery of 5-fluorouracil without being released in upper gastrointestinal region for the safe and effective management of colon cancer.